1939
DOI: 10.1152/ajplegacy.1939.126.3.661
|View full text |Cite
|
Sign up to set email alerts
|

The Coagulant Action of Crystalline Trypsin, Cephalin and Lung Extracts

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1945
1945
1969
1969

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Trypsin activation (21,22). To 1 ml of a 125 pg/ml solution of normal or patient II-7 "step 3" prothrombin were added 0.1 ml of 0.1 M CaCi, and 0.1 ml of a 50 pug/ml solution of trypsin in 0.001 M HCU.…”
Section: Prothrombin Activationmentioning
confidence: 99%
“…Trypsin activation (21,22). To 1 ml of a 125 pg/ml solution of normal or patient II-7 "step 3" prothrombin were added 0.1 ml of 0.1 M CaCi, and 0.1 ml of a 50 pug/ml solution of trypsin in 0.001 M HCU.…”
Section: Prothrombin Activationmentioning
confidence: 99%
“…There have been reports that intravenous trypsin caused shock (16), intravascular coagulation (17,19) local necrosis (18), sloughing of tissue (18), and was generally "too toxic for intravenous use" (19). Occasionally, shock did appear when doses exceeding 150,000 units of trypsin were given to rabbits, or greater than 750,000 units were given to dogs.…”
Section: ) Experimental Production Of Thrombi In Rabbits Andmentioning
confidence: 99%
“…The coagulant action of trypsin is more indirect, and they concluded that it activates prothrombin, thus appearing to behave like "thrombokinase," which, they suggested, might itself be a proteolytic enzyme. Ferguson and Erickson (73) showed that the action of trypsin on prothrombin is potentiated by "cephalin" and calcium ions. A similar analogy was provided by the venom of the Russell's viper which also required both calcium ions and phospholipid for its immensely powerful coagulant action on plasma (153,156,260).…”
Section: Introductionmentioning
confidence: 99%